Analog circuits cookbook - Hickman, Ian. (Oxford ; Boston : Newnes, 1999)
Analog Circuits Cookbook is a collection of tried and tested recipes form the masterchef of analog and RF design. Based on articles from Electronics World, this book provides a diet of high quality design techniques and applications, and proven ciruit designs, all concerned with the analog, RF and interface fields of electronics. Ian Hickman uses illustrations and examples rather than tough mathematical theory to present a wealth of ideas and tips based on his own workbench experience. This second edition includes 10 of Hickman's latest articles, alongside 20 of his most popular classics. The new material includes articles on power supplies, filters using negative resistance, phase noise and video surveillance systems. Essential reading for all circuit design professionals and advanced hobbyists Contains 10 of Ian Hickman's latest articles, alongside 20 of his most popular classics.
Passive components; Passive circuits; Active components; Audio frequency signals and reproduction; Passive signal processing and signal transmission; Active signal processing in the frequency domain; Active signal processing in the time domain; Radio frequency circuits; Signal sources; Power supplies; Tricks of the trade; Appendices; Index.
Includes bibliographical references and index.
Keywords: Analog electronic systems; Electronic circuits; Electronic books